Customer Satisfaction in Islamic Banking: Analyzing the Key Drivers in Indonesia - Anisa, May Nur; Alrasyid, Harun; Taqwiem, Ahsani (Maliki Islamic Economics Journal, 2024)
This study investigates the factors influencing customer satisfaction in Indonesian Islamic banks, specifically focusing on Bank Syariah Indonesia (BSI). Employing a quantitative method with multiple regression linier and purposive sampling technique, the study gathered data from 100 respondents who are customers of Bank Syariah Indonesia. Data collection was conducted by directly distributing questionnaires to these customers. The results show that service quality has a significant impact on customer satisfaction, indicating that higher service standards lead to increased satisfaction among customers. Additionally, price perception significantly affects customer satisfaction, suggesting that competitive and fair pricing enhances customer contentment. However, the study finds that convenience does not have a significant influence on customer satisfaction. The findings of this study suggest that Islamic banks should prioritize improving service quality and maintaining competitive pricing to boost customer satisfaction. While convenience is important, it may not be the primary driver of satisfaction for customers of Islamic Banking. These insights can help Islamic banks formulate strategies to enhance customer experiences. This study provides valuable insights into the key drivers of customer satisfaction in the context of Indonesian Islamic banking.